DEVELOPMENT OF ISLAMIC ACTIVITY BASED ECONOMY - Afief, Muhammad (Universitas Djuanda Bogor, 2016)
Real Working Lecture (KKN) is subject intrakurikuler held by all colleges require students tointeract with the community and the surrounding environment directly with the aim ofincreasing the capability and knowledge of students as a preparation to live in thecommunity after graduation. KKN also a form of real devotion to the community collegestudents, after getting the lecture material that can be useful in society itself. KKNimplementation is expected to help the environment and improve human resources topeople and students in the use and management of available resources. Independent KKNstudents to empower the villagers and village Mekarjaya Kabandungan by directing anddriving force to always do the activities of Islamic economics in terms of both worship andmuamalah. Development of Shariah-based economic activity is also seen the potential ofavailable resources both human and natural resources. Human resources mobilized anddirected to be more motivated to do things, which is based on sharia and natural resourcesprocessed and developed in order to provide benefit in the form of an increase in economicterms. Thus, the activities undertaken by the community will always be targeted and basedon sharia in terms of both physical and non-physical.